2016
DOI: 10.1177/1087054713479665
|View full text |Cite
|
Sign up to set email alerts
|

Case Series

Abstract: Based on the initial data, this intervention shows promise as an effective and feasible treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…According to the obtained results, children with ADHD showed poorer ability than normal group in terms of continuous attention on a task. This result is aligned with a study in (2017) confirming that children with attention deficithyperactivity have deficit in attention function (16). In addition, Bigura et al (2016) showed that deficit in some executive functions such as attention may be associated with poor performance in school of the group of children (13).…”
Section: Discussionsupporting
confidence: 85%
“…According to the obtained results, children with ADHD showed poorer ability than normal group in terms of continuous attention on a task. This result is aligned with a study in (2017) confirming that children with attention deficithyperactivity have deficit in attention function (16). In addition, Bigura et al (2016) showed that deficit in some executive functions such as attention may be associated with poor performance in school of the group of children (13).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the authors noted that improving the child's sleep also resulted in improvements in hyperactivity and/or conduct problems in their sample. Vetrayan et al examined the impact of a 4-week behavioral sleep program on six children (aged 6-12 years) who were actively taking stimulant medications for their ADHD symptoms [80]. The intervention was effective in reducing sleep onset latency and bedtime resistance, and parents viewed the treatment as a positive experience.…”
Section: Patients With Psychiatric Co-morbiditiesmentioning
confidence: 99%